Epigenetic Codes Programing Class Switch Recombination - Vaidyanathan, Bharat; Chaudhuri, Jayanta (Frontiers in Immunology, 2015)
Class switch recombination imparts B cells with a fitness-associated adaptive advantage during a humoral immune response by using a precision-tailored DNA excision and ligation process to swap the default constant region gene of the antibody with a new one that has unique effector functions. This secondary diversification of the antibody repertoire is a hallmark of the adaptability of B cells when confronted with environmental and pathogenic challenges. Given that the nucleotide sequence of genes during class switching remains unchanged (genetic constraints), it is logical and necessary therefore, to integrate the adaptability of B cells to an epigenetic state, which is dynamic and can be heritably modulated before, after or even during an antibody-dependent immune response. Epigenetic regulation encompasses heritable changes that affect function (phenotype) without altering the sequence information embedded in a gene, and include histone, DNA and RNA modifications. Here, we review current literature on how B cells use an epigenetic code language as a means to ensure antibody plasticity in light of pathogenic insults.